2016
DOI: 10.1002/ajoc.201600288
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Templated Asymmetric Catalysis: (Z)‐1‐Bromo‐1‐Nitrostyrenes as Versatile Substrates for Friedel–Crafts Alkylation of Indoles

Abstract: An asymmetricF riedel-Crafts alkylation of indoles with (Z)-1-bromo-1-nitrostyrenes, which is efficiently catalyzed by an umber of hydrogenb ond interactions with the ligand sphere of bis-cyclometalated iridium complexes, has been reported. The proposed transition state exploits ah ydrogen bond network, which is illustrated by the co-crystal structure of am odel catalyst with an analog of the nitro substrate. The bromof unctional group not only plays an important role for achieving ah igh asymmetric induction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…1316 The reaction of β-amino-α-bromo nitroalkane ( 3g ), and α-amino acid-derived acyl hydrazide ( 2o ), provide the enantiopure oxadiazole products ( 14 and 15 ), demonstrating that no racemization of either chiral α-bromo nitroalkane or amino acid hyrazide occurred during the oxadiazole formation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1316 The reaction of β-amino-α-bromo nitroalkane ( 3g ), and α-amino acid-derived acyl hydrazide ( 2o ), provide the enantiopure oxadiazole products ( 14 and 15 ), demonstrating that no racemization of either chiral α-bromo nitroalkane or amino acid hyrazide occurred during the oxadiazole formation.…”
Section: Resultsmentioning
confidence: 99%
“…Chiral, nonracemic α-bromo nitroalkanes are increasingly available in as little as a single step using enantioselective catalysis and bromonitromethane reagent. 13 16 The reaction of β-amino-α-bromo nitroalkane ( 3g ), and α-amino acid-derived acyl hydrazide ( 2o ), provide the enantiopure oxadiazole products ( 14 and 15 ), demonstrating that no racemization of either chiral α-bromo nitroalkane or amino acid hyrazide occurred during the oxadiazole formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…96 Since then, these catalysts have been widely employed in the enantioselective conjugate reduction of b,b-disubstituted nitroalkenes with Hantzsch esters and Friedel-Crafts alkylation of indoles with b,b-disubstituted nitroalkenes (Schemes 8-11). 96,97,108,[111][112][113][114] They demonstrated that the iridium(III) complex K-4 efficiently catalysed the enantioselective reduction of b,b-disubstituted nitroalkenes with a Hantzsch ester as the reducing agent at remarkably low catalyst loadings (up to 0.1 mol%) (Scheme 8). 96 The corresponding reduced (R)-nitroalkane products were obtained in high yields with excellent enantioselectivities (93-99% ee) (Scheme 8).…”
Section: Chiral-at-metal Iridium(iii) Complexes As Dual Hydrogen Bond Donor/acceptor Catalystsmentioning
confidence: 99%
“…Chiral stereochemically inert, coordinatively saturated metal complexes of Co, Cr, Rh, Ir or Ru presented a perspective class of "organic catalysts in disguise" which were applied in various asymmetric organic reactions [1][2][3][4]. In these complexes, the metal center can play several important roles: (1) to activate the coordinated ligands converting them into efficient hydrogen bond donors/acceptors ; (2) to serve as a chiral center (metal-centered chirality) providing a well-defined chiral environment [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] (in case of octahedral geometry of the complexes due to the mutual meridional arrangement of the chiral or achiral ligands around the metal ion with Λ-(left-handed propeller) or ∆configurations (right-handed propeller)) [1][2][3][4][5][6][7][8][9][10][11][13][14][15][16][17][18][19][20][21][22]…”
Section: Introductionmentioning
confidence: 99%